Optimisation of environmental gas cleaning routes for solid wastes cogeneration systems - Part I - Analysis of waste incineration steam cycle - Holanda, Marcelo R.; Balestieri, José Antônio Perrella [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Research of advanced technologies for energy generation contemplates a series of alternatives that are introduced both in the investigation of new energy sources and in the improvement and/or development of new components and systems. Even though significant reductions are observed in the amount of emissions, the proposed alternatives require the use of exhaust gases cleaning systems. The results of environmental analyses based on two configurations proposed for urban waste incineration are presented in this paper; the annexation of integer (Boolean) variables to the environomic model makes it possible to define the best gas cleaning routes based on exergetic cost minimisation criteria. In this first part, the results for steam cogeneration system analysis associated with the incineration of municipal solid wastes (MSW) is presented. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: gas cleaning routes; municipal solid wastes; cogeneration system; steam cycle; optimisation; environomic analysis